2015
DOI: 10.1371/journal.pone.0138201
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin Extracted from Black Soybean Seed Coats Prevents Autoimmune Arthritis by Suppressing the Development of Th17 Cells and Synthesis of Proinflammatory Cytokines by Such Cells, via Inhibition of NF-κB

Abstract: IntroductionOxidative stress plays a role in the pathogenesis of rheumatoid arthritis (RA). Anthocyanin is a plant antioxidant. We investigated the therapeutic effects of anthocyanin extracted from black soybean seed coats (AEBS) in a murine model of collagen-induced arthritis (CIA) and human peripheral blood mononuclear cells (PBMCs) and explored possible mechanisms by which AEBS might exert anti-arthritic effects.Material and MethodsCIA was induced in DBA/1J mice. Cytokine levels were measured via enzyme-lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 35 publications
1
30
0
Order By: Relevance
“…Additionally, several studies conducted on other major crop plants have also revealed an association between the seed color and phenolic components (Zhang et al 2010;Shao et al 2011;Wang et al 2015). Although higher flavonoid content was reported in the seed coats than in the embryos of soybean and rice (Bordiga et al 2014;Min et al 2015), it has been emphasized that the type and quantity of flavonoids in seed coats and embryos may be related to plant genotype (Hou et al 2017). Furthermore, Shen et al (2009) andShao et al (2014) found that black-and red-colored rice grains contain higher flavonoid content than white-colored grains.…”
Section: Agro-morphological Characterization For Rutin and Quercetin mentioning
confidence: 99%
“…Additionally, several studies conducted on other major crop plants have also revealed an association between the seed color and phenolic components (Zhang et al 2010;Shao et al 2011;Wang et al 2015). Although higher flavonoid content was reported in the seed coats than in the embryos of soybean and rice (Bordiga et al 2014;Min et al 2015), it has been emphasized that the type and quantity of flavonoids in seed coats and embryos may be related to plant genotype (Hou et al 2017). Furthermore, Shen et al (2009) andShao et al (2014) found that black-and red-colored rice grains contain higher flavonoid content than white-colored grains.…”
Section: Agro-morphological Characterization For Rutin and Quercetin mentioning
confidence: 99%
“…Research on soybean and rice has shown that the flavonoid content in the seed coat is higher than in the embryo per unit of seeds (Bordiga et al 2014, Min et al 2015. Research has also indicated that the flavonol content in rice embryos is much higher than that in seed coats (Galland et al 2014); however, few studies have analyzed the flavonoid content in peanut seed embryos.…”
Section: Hou Et Almentioning
confidence: 99%
“…Currently, many studies are involved in CA, regulating effects of inflammatory reaction and apoptotic activity. 48,49 Therefore, regarding the significant ability of inflammatory inhibition and apoptotic induction in liver cancer cells of our nanoparticle CA, it is illustrated that the natural compound of nanoparticle CA has high potential to suppress the liver cancer growth and could be used as a promising anticancer drug. However, prospective researches should be conducted for full understanding of the functional mechanism of CA nanoparticle at the molecular level.…”
mentioning
confidence: 99%